Agile service oriented shipping companies in the container terminal - Liu, Wei; Xu, Huan; Zhao, Xin (Transport, 2009)
Agility is regarded as one of the core capabilities and the developing trend of supply chains and their enterprises. Along with the development of economical globalization, supply chain management and containerization as well as container ports as a part of supply chain take more roles like logistics or distribution centers. Under this background, the container terminal should have superior response and develop agility. The main goal of this paper is to emphasize and illustrate the importance and imminence of implementing agility in container terminals. To achieve this goal, the analysis of the economies of scale in the container terminal is presented. In this paper, however, more attention will be paid to agile service oriented shipping companies. The concept and characters of agile service in the container terminal is illustrated. The paper also focuses on the agile organizational structure of the container terminal. Finally, the fuzzy quality synthetic evaluation method is given to evaluate the performance level of agile service in container terminal oriented shipping companies.First published online: 27 Oct 2010